Динамiка коротких електронних згусткiв та збуджених ними кiльватерних полiв у плазмi за вiдсутностi та за наявностi поздовжнього магнiтного поля - Anisimov, I. O.; Shcherbinin, M. A. (Publishing house "Academperiodika", 2019)
Using the computer simulation, the influence of a longitudinal magnetic field on the wakefield excitation in plasma by an initially cylindrical electron bunch with the length equal to the wake wavelength and the inverse influence of excited fields on the bunch dynamics have been considered. It is shown that the magnetic field can suppress the radial defocusing of the bunch and increase the length of the region, in which the wake waves are excited, as well as the amplitude of those waves.